Formable high strength aluminum alloy product and method for producing same
Patent Information
- Application Number
- JP2021547066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-23
- Filing Date
- 2019-10-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2039-10-23
AI Technical Summary
Existing aluminum alloys face a trade-off between high strength and formability, with high-strength alloys often compromising formability and vice versa, making them unsuitable for applications requiring both properties.
A method involving continuous casting, controlled hot rolling, and downstream processing steps, including homogenization, hot rolling, coil cooling, and aging, to produce aluminum alloys with specific alloying elements (Zr, Mg, and Zn) that enhance both strength and formability.
The method results in aluminum alloys with increased elongation and yield strength after aging, achieving high strength without compromising formability, suitable for complex shape formation in automotive, transportation, and electronics applications.
Smart Images

Figure 00000029_0000 
Figure 00000029_0001 
Figure 00000029_0002
Abstract
Description
Technical Field
[0001] Cross - Reference to Related Applications This application claims the benefit and priority of U.S. Patent Application No. 62 / 749,158, filed on October 23, 2018, which is hereby incorporated by reference in its entirety.
[0002] This disclosure relates to the field of aluminum alloys, and more particularly, to methods of making and processing aluminum alloy products.
Background Art
[0003] High - strength aluminum alloys are desired, among other things, for improved product performance in many applications, such as automotive and other transportation applications (e.g., but not limited to, trucks, trailers, trains, aerospace applications, and marine applications), as well as in electronics applications. In some cases, such alloys must exhibit, among other properties, high strength and high formability (e.g., the ability to be formed into a desired shape). Achieving aluminum alloy products with high strength often results in a loss of formability. Conversely, achieving aluminum alloy products with high formability often results in products of lower strength.
Summary of the Invention
[0004] Embodiments of the subject matter of the present invention are defined by the claims, not this summary. This summary is a high - level overview of various aspects of the invention and introduces some of the concepts further described in the following detailed description section. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used in isolation to determine the scope of the claimed subject matter. The subject matter should be understood by reference to the entire specification, any or all of the drawings, and the appropriate portions of each claim.
[0005] This specification describes a method for producing a formable high-strength aluminum alloy product, the method comprising: continuously casting a molten aluminum alloy composition to provide a cast aluminum alloy product having a casting outlet temperature, wherein the molten aluminum alloy composition comprises an aluminum alloy containing at least 0.1% by weight of Zr, at least 2% by weight of Mg, and Zn as a major alloying element other than Al; cooling the cast aluminum alloy product to a temperature below the casting outlet temperature of 20°C to 50°C to provide a heat-stabilized cast aluminum alloy product; hot rolling the heat-stabilized cast aluminum alloy product to provide an aluminum alloy hot band; coiling the aluminum alloy hot band to provide a hot band coil; cooling the hot band coil to a temperature of 200°C to 400°C; further processing the hot band coil to provide a final gauge aluminum alloy product; and solution-treating the final gauge aluminum alloy product. In some examples, the molten aluminum alloy composition contains a ratio of Zn to Mg of 1.2 to 3. In certain cases, the method comprises hot rolling a cast aluminum alloy product, further comprising hot rolling a heat-stabilized cast aluminum alloy product to a hot-rolling input temperature. In some cases, the hot-rolling of the heat-stabilized cast aluminum alloy product reduces the thickness of the heat-stabilized cast aluminum alloy product by at least 30% (e.g., 40% to 50%).
[0006] In some cases, further processing steps may include homogenizing the hot band coil to provide a homogenized hot band coil, and hot-rolling the homogenized hot band coil to provide a final gauge aluminum alloy product. In other cases, further processing steps may include homogenizing the hot band coil to provide a homogenized hot band coil, cooling the homogenized hot band coil, and cold-rolling the homogenized hot band coil to provide a final gauge aluminum alloy product. In yet other cases, further processing steps may include cold-rolling the hot band coil to provide a final gauge aluminum alloy product. The homogenization step may include heating the aluminum alloy hot band to a homogenization temperature of at least about 450°C, and holding the aluminum alloy hot band at the homogenization temperature of at least about 450°C for a period of at least about 90 minutes (e.g., about 90 minutes to about 150 minutes).
[0007] The method may further include a step of pre-aging the final gauge aluminum alloy product. Pre-aging may include heating the final gauge aluminum alloy product to a pre-aging temperature of about 50°C to about 150°C and maintaining the pre-aging temperature for a period of about 1 hour to about 24 hours. The method may further include aging the final gauge aluminum alloy product to achieve a yield strength of at least about 400 MPa. Aging may include one or more of the following: natural aging, artificial aging, paint baking, and post-form heat treatment. In some cases, natural aging may include maintaining the final gauge aluminum alloy product at room temperature for a period of about 1 day to about 12 weeks. Artificial aging may include heating the final gauge aluminum alloy product to an artificial aging temperature of about 100°C to about 250°C and maintaining the artificial aging temperature for a period of about 1 to about 72 hours (e.g., about 12 hours to about 72 hours). Paint baking may include heating the final gauge aluminum alloy product to a paint baking temperature of approximately 75°C to 250°C and maintaining the paint baking temperature for a period of approximately 15 minutes to 3 hours. Post-forming heat treatment may include heating the final gauge aluminum alloy product to a post-forming heat treatment temperature of approximately 100°C to 250°C and maintaining the post-forming heat treatment temperature for a period of approximately 1 hour to 24 hours.
[0008] Aluminum alloy products prepared according to the methods described herein are also described herein. Aluminum alloy products can achieve increases in both elongation and yield strength after aging compared to aluminum alloy products before any aging (e.g., before natural aging, artificial aging, paint baking, or post-forming heat treatment). The increase in elongation can be at least about 1% (e.g., about 1.5% to about 5%). The increase in yield strength can be at least about 15 MPa (e.g., about 15 MPa to about 25 MPa).
[0009] Other objects and advantages of the present invention will become apparent from the following detailed description of non-limiting embodiments of the present invention and from the drawings. [Brief explanation of the drawing]
[0010] [Figure 1A] This is a schematic diagram illustrating the aluminum alloy processing method described herein. [Figure 1B] This is a schematic diagram illustrating the aluminum alloy processing method described herein. [Figure 1C] This is a schematic diagram illustrating the aluminum alloy processing method described herein. [Figure 2] This graph shows the strength and elongation properties of aluminum alloy products processed by the methods described herein. [Figure 3] This graph shows the strength and elongation properties of aluminum alloy products processed by the methods described herein. [Figure 4] This graph shows the strength and elongation properties of aluminum alloy products processed by the methods described herein. [Figure 5] This graph shows the strength and elongation properties of aluminum alloy products processed by the methods described herein. [Figure 6] This graph shows the strength and elongation properties of aluminum alloy products processed by the methods described herein. [Figure 7] This specification includes optical microscope (OM) images showing the particle distribution of undissolved intermetallic particles in an aluminum alloy product treated by the method described herein. [Figure 8] This specification includes OM micrographs showing the crystalline structure and undissolved intermetallic particles in an aluminum alloy product treated by the method described herein. [Figure 9] This is a schematic diagram illustrating the aluminum alloy processing method described herein. [Figure 10] This graph shows the effect of natural aging on the strength properties of aluminum alloy products treated by the methods described herein. [Figure 11] This graph shows the effect of natural aging on the elongation properties of aluminum alloy products treated by the method described herein. [Figure 12] This graph shows the effect of natural aging on the elongation properties of aluminum alloy products treated by the method described herein. [Figure 13] This graph shows the effect of various post-quenching natural aging processes on the strength properties of aluminum alloy products treated by the methods described herein. [Figure 14] This graph shows the effect of various post-quenching natural aging processes on the strength properties of aluminum alloy products treated by the methods described herein. [Figure 15] This graph shows the effect of various post-quenching natural aging processes on the elongation properties of aluminum alloy products treated by the methods described herein. [Figure 16] This graph shows the effect of various post-quenching natural aging processes on the elongation properties of aluminum alloy products treated by the methods described herein. [Figure 17] This graph shows the effect of various post-quenching natural aging processes on the elongation properties of aluminum alloy products treated by the methods described herein. [Figure 18] This graph shows the effect of various post-quenching natural aging processes on the elongation properties of aluminum alloy products treated by the methods described herein. [Figure 19] This graph shows the effect of various post-quenching natural aging processes on the bending properties of aluminum alloy products treated by the methods described herein. [Figure 20] This graph shows the effect of various post-quenching natural aging processes on the bending properties of aluminum alloy products treated by the methods described herein. [Figure 21] This graph shows the effect of artificial aging on the strength properties of aluminum alloy products treated by the method described herein. [Figure 22] This graph shows the effect of various post-quenching artificial aging processes on the strength properties of aluminum alloy products treated by the methods described herein. [Figure 23]A graph showing the effects of various post-quenching artificial aging on the strength characteristics of aluminum alloy products processed by the method described in this specification. [Figure 24] Contains an OM micrograph showing the particle distribution of undissolved intermetallic particles in an aluminum alloy product processed by the method described in this specification. [Figure 25] Contains an OM micrograph showing the crystal structure and undissolved intermetallic particles in an aluminum alloy product processed by the method described in this specification. [Figure 26] A graph showing the strength characteristics over time of an aluminum alloy product processed by the method described in this specification. [Figure 27] A graph showing the elongation characteristics over time of an aluminum alloy product processed by the method described in this specification. [Figure 28] A graph showing the elongation characteristics over time of an aluminum alloy product processed by the method described in this specification.
Embodiments for Carrying Out the Invention
[0011] This specification describes a method for processing high-strength aluminum alloy products using a continuous casting process, a modified hot rolling schedule, and various downstream processing steps, as well as aluminum alloy products prepared and processed according to this method. The aluminum alloy processing method described herein provides a more efficient method for producing aluminum alloy products with high-strength and formability properties required by end-users (e.g., original equipment manufacturers (OEMs)). Typically, high-strength aluminum alloy products can suffer from low formability due to hardening that occurs during aging practices. Similarly, highly formable aluminum alloy products may lack the strength required for use as structural components in automotive, transportation, electronics, professional applications, or any combination thereof. However, the aluminum alloy products described herein exhibit high-strength properties without compromising formability, and in some cases, with improved formability. The aluminum alloy products described herein are also susceptible to the effects of room-temperature forming, enabling the achievement of complex shapes as desired, for example, in the automotive industry and other industries.
[0012] Definition and Description As used herein, the terms “invention,” “the invention,” “this invention,” and “the present invention” are intended to broadly refer to all the subject matter of this patent application and the following claims. It should be understood that the specification containing these terms does not limit the subject matter described herein, nor does it limit the meaning or scope of the following claims.
[0013] This description refers to alloys identified by aluminum industry names such as "Series" or "7xxx." For an understanding of the most commonly used numbering system for naming and identifying aluminum and its alloys, see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Composition Limits for Aluminum Alloys in the Form of Castings and Ingot" (both published by the Aluminum Association).
[0014] The following aluminum alloys are described in terms of their elemental composition in weight percentages (wt%) based on the total weight of the alloy. In specific examples of each alloy, the remainder is aluminum, and the total maximum weight of impurities is 0.15 wt%.
[0015] As used herein, the meanings of "a," "an," or "the" include singular and plural references unless the context explicitly indicates otherwise.
[0016] As used herein, a sheet generally has a thickness greater than approximately 15 mm and a maximum of approximately 200 mm. For example, a plate can mean an aluminum alloy product having a thickness greater than approximately 15 mm, greater than approximately 20 mm, greater than approximately 25 mm, greater than approximately 30 mm, greater than approximately 35 mm, greater than approximately 40 mm, greater than approximately 45 mm, greater than approximately 50 mm, greater than approximately 100 mm, or a maximum of approximately 200 mm.
[0017] As used herein, a sheet (also called a sheet plate) generally has a thickness of approximately 4 mm to 15 mm. For example, a sheet can have a thickness of approximately 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, or 15 mm.
[0018] As used herein, a sheet generally refers to an aluminum alloy product having a thickness of less than approximately 4 mm. For example, a sheet may have a thickness of less than approximately 4 mm, less than approximately 3 mm, less than approximately 2 mm, less than approximately 1 mm, less than approximately 0.5 mm, less than approximately 0.3 mm, or less than approximately 0.1 mm.
[0019] This application makes references to the temper or grade of alloys. To understand the most commonly used descriptions of alloy grades, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". F temper or grade refers to the aluminum alloy as manufactured. O temper or grade refers to the aluminum alloy after annealing. T1 temper or grade refers to the aluminum alloy that has been cooled from hot work and naturally aged (e.g., at room temperature). T2 temper or grade refers to the aluminum alloy that has been cooled from hot work, cold work, and naturally aged. T3 temper or grade refers to the aluminum alloy that has been solution heat treated, cold work, and naturally aged. T4 temper or grade refers to the aluminum alloy that has been solution heat treated and naturally aged. T5 temper or grade refers to the aluminum alloy that has been cooled from hot work and artificially aged (at high temperatures). T6 temper or grade refers to the aluminum alloy that has been solution heat treated and artificially aged. T7 temper or temper refers to aluminum alloy that has been solution-heat treated and artificially overaged. T8x temper or temper refers to aluminum alloy that has been solution-heat treated, cold-treated and artificially aged. T9 temper or temper refers to aluminum alloy that has been solution-heat treated, artificially aged and cold-treated.
[0020] As used herein, terms such as “cast metal products,” “cast products,” and “cast aluminum alloy products” are interchangeable and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, by the use of a twin-belt caster, twin-roll caster, block caster, or any other casting machine), electromagnetic casting, hot top casting, or any other casting method.
[0021] As used herein, “room temperature” means a temperature between approximately 15°C and approximately 30°C, for example, approximately 15°C, approximately 16°C, approximately 17°C, approximately 18°C, approximately 19°C, approximately 20°C, approximately 21°C, approximately 22°C, approximately 23°C, approximately 24°C, approximately 25°C, approximately 26°C, approximately 27°C, approximately 28°C, approximately 29°C, or approximately 30°C.
[0022] All disclosures herein should be understood to encompass any endpoint and any subranges contained therein. For example, the described range "1 to 10" should be considered to encompass all subranges between (and including) the minimum value 1 and the maximum value 10; that is, all subranges begin with a minimum value greater than or equal to 1, e.g., 1 to 6.1, and end with a maximum value less than or equal to 10, e.g., 5.5 to 10.
[0023] Preparation and processing methods The method for producing a formable high-strength aluminum alloy product described herein includes casting a molten aluminum alloy composition (for example, by continuous casting), hot rolling the cast aluminum alloy product to provide an aluminum alloy hot band, coiling and cooling the aluminum alloy hot band to provide a hot band coil, and then providing a final gauge aluminum alloy product by one or more further processing steps.
[0024] In some cases, the processing method may include hot rolling, homogenization, hot rolling to a final gauge, and solution treatment. In other cases, the processing method may include hot rolling, homogenization, coil cooling, cold rolling to a final gauge, and solution treatment. In yet another case, the processing method may include hot rolling, coil cooling, cold rolling to a final gauge, and solution treatment. Any of the above processing methods can be combined with subsequent processing methods, including forming and further heat treatment, to provide high-strength and formable aluminum alloy products.
[0025] The aluminum alloy products described herein can be prepared from an aluminum alloy composition containing at least about 0.1 wt% zirconium (Zr), at least about 2 wt% magnesium (Mg), and zinc (Zn) as a major alloying element other than aluminum (Al) (e.g., at least about 3 wt%). Combined with the processing conditions described later, the presence of at least about 0.10 wt% Zr, at least about 2 wt% Mg, and Zn as a major alloying element (other than Al) yields aluminum alloy products with exceptional strength and formability. In some cases, the combination yields aluminum alloy products with high corrosion resistance.
[0026] In some cases, Zr may be present in amounts ranging from approximately 0.1% to 2% (e.g., approximately 0.15% to 1.5%, 0.2% to 1.3%, or 0.5% to 1%) based on the total weight of the aluminum alloy. For example, aluminum alloys can contain Zr in amounts of approximately 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.
[0027] In some cases, Mg can be present in amounts of at least about 2% (for example, about 2% to 5%, about 2.1% to 4.9%, about 2.2% to 4.8%, about 2.3% to 4.75%, about 2.4% to 4.7%, about 2.5% to 4.6%, about 2.75% to 4.5%, or about 3% to 4.25%). For example, aluminum alloys can contain Mg in amounts of approximately 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, or 5%.
[0028] As mentioned above, Zn can be the main alloying element other than Al in aluminum alloys. In some cases, Zn is present in amounts of at least about 3% (e.g., about 3% to about 20%, about 4.5% to about 18%, about 7.5% to about 15%, about 10% to about 15%, about 3.5% to about 10.5%, or about 4% to about 8%). For example, aluminum alloys are approximately 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, and 6.4%. %, approximately 6.5%, approximately 6.6%, approximately 6.7%, approximately 6.8%, approximately 6.9%, approximately 7%, approximately 7.1%, approximately 7.2%, approximately 7.3%, approximately 7.4%, approximately 7.5%, approximately 7.6%, approximately 7.7%, approximately 7.8%, approximately 7.9%, approximately 8%, approximately 8.1%, approximately 8.2%, approximately 8.3%, approximately 8.4%, approximately 8.5%, approximately 8.6%, approximately 8.7%, approximately 8.8%, approximately 8.9%, approximately 9%, approximately 9.1%, approximately 9.2%, approximately 9.3%, approximately 9.4%, approximately 9.5%, approximately 9.6%, approximately 9.7%, approximately 9.8%, approximately 9.9%, approximately 10%, approximately 10. 1%, approximately 10.2%, approximately 10.3%, approximately 10.4%, approximately 10.5%, approximately 10.6%, approximately 10.7%, approximately 10.8%, approximately 10.9%, approximately 11%, approximately 11.1%, approximately 11.2%, approximately 11.3%, approximately 11.4%, approximately 11.5%, approximately 11.6%, approximately 11.7%, approximately 11.8%, approximately 11.9%, approximately 12%, approximately 12.1%, approximately 12.2%, approximately 12.3%, approximately 12.4%, approximately 12.5%, approximately 12.6%, approximately 12.7%, approximately 12.8%, approximately 12.9%, approximately 13%, approximately 13.1%, approximately 13.2%, Approximately 13.3%, 13.4%, 13.5%, 13.6%, 13.7%, 13.8%, 13.9%, 14%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9%, 15%, 15.1%, 15.2%, 15.3%, 15.4%, 15.5%, 15.6%, 15.7%, 15.8%, 15.9%, 16%, 16.1%, 16.2%, 16.3%, 16.4%, approximately 16.5%, approximately 16.6%, approximately 16.7%, approximately 16.8%, approximately 16.9%, approximately 17%, approximately 17.1%, approximately 17.2%, approximately 17.3%, approximately 17.4%, approximately 17.5%, approximately 17.6%, approximately 17.7%, approximately 17.8%, approximately 17.9%, approximately 18%, approximately 18.1%, approximately 18.2%, approximately 18.3%, It can contain Zn in amounts of approximately 18.4%, 18.5%, 18.6%, 18.7%, 18.8%, 18.9%, 19%, 19.1%, 19.2%, 19.3%, 19.4%, 19.5%, 19.6%, 19.7%, 19.8%, 19.9%, or 20%.
[0029] In some cases, the amounts of Zn and Mg are adjusted relative to each other. For example, if the amount of Mg is about 3.5% or more, the amount of Zn in the composition can be less than 7% (e.g., less than 6.9%, less than 6.8%, less than 6.7%, less than 6.6%, less than 6.5%, less than 6.4%, less than 6.3%, less than 6.2%, less than 6.1%, less than 6%, less than 5.9%, less than 5.8%, less than 5.7%, less than 5.6%, less than 5.5%, less than 5.4%, less than 5.3%, less than 5.2%, less than 5.1%, less than 5%, less than 4.9%, less than 4.8%, less than 4.7%, less than 4.6%, or less than 4.5%). Adjusting the amounts of Zn and Mg in this way is a factor in achieving the high strength and formability shown by the aluminum alloy products described herein. While not theoretically bound, when used as an alloying element in aluminum, Mg can increase both strength and formability. By incorporating Zn and Mg in a Zn-to-Mg ratio of approximately 1.2 to 3 (i.e., weight percentage of Zn / weight percentage of Mg), strength can be further increased and excellent formability can be imparted. In some cases, incorporating certain amounts of Zn and Mg can result in Zn-to-Mg ratios of approximately 1.2 to 2.7, 1.3 to 2.5, 1.4 to 2.2, 1.5 to 2, or 1.2 to 1.7. For example, the Zn-to-Mg ratio can be approximately 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, or anywhere in between.
[0030] In some non-limiting cases, Zn and Mg can be combined to increase the corrosion resistance exhibited by aluminum alloy products. In some cases, the total amount of Zn and Mg present in the composition is about 5.8% to about 25% (e.g., about 6% to about 20%, about 6.5% to about 18%, or about 7% to about 15%). For example, the total amount of Zn and Mg can be approximately 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 13.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, or 25%.
[0031] Optionally, the aluminum alloy for preparing the aluminum alloy products described herein may further contain copper (Cu), iron (Fe), manganese (Mn), silicon (Si), titanium (Ti), and chromium (Cr), as well as one or more impurities, with Al in the remainder.
[0032] In some embodiments, the aluminum alloy contains about 0.1% to about 3% (e.g., about 0.1% to about 2.6%, or about 0.15% to about 2%) of Cu based on the total weight of the alloy. For example, the alloy may contain about 0.1%, about 0.2%, about 0.3%, about 0.4%, about 0.5%, about 0.6%, about 0.7%, about 0.8%, about 0.9%, about 1%, about 1.1%, about 1.2%, about 1.3%, about 1.4%, about 1.5%, about 1.6%, about 1.7%, about 1.8%, about 1.9%, about 2%, about 2.1%, about 2.2%, about 2.3%, about 2.4%, about 2.5%, about 2.6%, about 2.7%, about 2.8%, about 2.9%, or about 3% Cu. In some cases, Cu is not present in the alloy (i.e., it is 0%).
[0033] In some embodiments, the aluminum alloy contains up to approximately 0.25% (e.g., approximately 0% to approximately 0.15%, or approximately 0.05% to approximately 0.10%) of Fe based on the total weight of the alloy. For example, the alloy may contain approximately 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, or approximately 0.25% Fe. In some cases, Fe is not present in the alloy (i.e., it is 0%).
[0034] In some embodiments, the aluminum alloy contains Mn, Si, Ti, and / or Cr in amounts up to about 0.2% (e.g., 0% to about 0.1%, or about 0.05% to about 0.15%) based on the total weight of the alloy. For example, the alloy may contain about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.1%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, or about 0.2% of each of Mn, Si, Ti, and / or Cr. In some cases, one or more of Mn, Si, Ti, or Cr may not be present in the alloy (i.e., they may be present at 0%).
[0035] Optionally, aluminum alloys may also contain other trace elements, sometimes called impurities, in amounts of approximately 0.05%, 0.04%, 0.03%, 0.02%, or 0.01%, respectively. These impurities may include, but are not limited to, V, Ni, Sn, Ga, Ca, Bi, Na, Pb, or combinations thereof. Therefore, V, Ni, Sn, Ga, Ca, Bi, Na, or Pb may be present in the alloy in amounts of approximately 0.05%, 0.04%, 0.03%, 0.02%, or 0.01%. The total amount of all impurities does not exceed approximately 0.15% (e.g., approximately 0.10%). The remaining proportion of the alloy is aluminum.
[0036] Optionally, aluminum alloy products suitable for use in the methods described herein include aluminum alloys of the 7xxx series. In some cases, the aluminum alloys of the 7xxx series for use in the methods described herein may be aluminum alloys of the 7xxx series registered with the Aluminum Society, which may be optionally modified to include certain amounts of Zr, Mg, Zn, and / or any other elements mentioned above. Examples of aluminum alloys of the 7xxx series include AA7003, AA7004, AA7204, AA7005, AA7108, AA7108A, AA7009, AA7010, AA7012, AA7014, AA70, which may be optionally modified to include at least about 0.1 wt% Zr, at least about 2.8 wt% magnesium (Mg), and zinc (Zn) as the main alloying element. 15, AA7016, AA7116, AA7017, AA7018, AA7019, AA7019A, AA7020, AA7021, AA7022, AA7122, AA7023, AA702 4, AA7025, AA7026, AA7028, AA7029, AA7129, AA7229, AA7030, AA7031, AA7032, AA7033, AA7034, AA7035, A A7035A, AA7036, AA7136, AA7037, AA7039, AA7040, AA7140, AA7041, AA7042, AA7046, AA7046A, AA7047, A A7049, AA7049A, AA7149, AA7249, AA7349, AA7449, AA7050, AA7050A, AA7150, AA7055, AA7155, AA7255, AA Examples include 7056, AA7060, AA7064, AA7065, AA7068, AA7168, AA7072, AA7075, AA7175, AA7475, AA7076, AA7178, AA7278, AA7278A, AA7081, AA7181, AA7085, AA7185, AA7090, AA7093, AA7095, AA7099, or AA7199.
[0037] In some embodiments, the alloy is a monolithic alloy. In some embodiments, the alloy is a clad aluminum alloy having one core layer and one or two clad layers. In some cases, the core layer may differ from one or both clad layers. The core layer may be, for example, an aluminum alloy as described herein (e.g., an aluminum alloy containing at least about 0.1 wt% Zr, at least about 2 wt% Mg, and Zn as the main alloying element other than Al).
[0038] casting The alloy can be cast using any suitable casting process. For example, molten aluminum alloy compositions, including the aluminum alloys described herein, can be cast using a continuous casting (CC) process, including but not limited to the use of a twin-belt caster, twin-roll caster, or block caster. In some embodiments, the casting process is carried out using a CC process to form cast products such as billets, slabs, or strips.
[0039] In some cases, the resulting cast aluminum alloy product can exit the casting machine at a temperature of approximately 370°C to approximately 450°C (e.g., casting machine exit temperature). For example, the casting aluminum alloy product may have a casting machine exit temperature of approximately 370°C, approximately 380°C, approximately 390°C, approximately 400°C, approximately 410°C, approximately 420°C, approximately 430°C, approximately 440°C, approximately 450°C, or any location in between.
[0040] The resulting cast aluminum alloy product can have a thickness of approximately 5 mm to 50 mm (for example, approximately 10 mm to 45 mm, approximately 15 mm to 40 mm, or approximately 20 mm to 35 mm), for example, approximately 10 mm. For example, cast aluminum alloy products can be approximately 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 16mm, 17mm, 18mm, 19mm, 20mm, 21mm, 22mm, 23mm, 24mm, 25mm, 26mm, 27mm, 28mm, 29mm, 30mm, 31mm, 32mm, 33mm, 34mm, 35mm, 36mm, 37mm, 38mm, 39mm, 40mm, 41mm, 42mm, 43mm, 44mm, 45mm, 46mm, 47mm, 48mm, 49mm, or 50mm thick.
[0041] Next, the cast aluminum alloy product can be subjected to further processing steps. In some non-limiting cases, the processing method includes hot rolling, coiling, coil cooling, further processing steps described below, solution treatment, and / or aging. In some cases, the further processing may include homogenization and hot rolling to the final gauge. In other cases, the further processing may include homogenization, cooling, and cold rolling to the final gauge. In yet other cases, the further processing may include cold rolling to the final gauge.
[0042] Any post-casting treatments In certain embodiments, after the casting process, the cast aluminum alloy product may be subjected to optional cooling, homogenization, and / or reheating. In some cases, cooling is performed to bring the temperature of the cast aluminum alloy product to about 20°C to about 50°C below the casting machine outlet temperature. In some cases, the casting machine outlet temperature may be about 400°C to about 430°C (for example, the casting machine outlet temperature may be about 400°C, 410°C, 420°C, or 430°C). In some cases, the cooling process provides a thermally stable cast aluminum alloy product. Cooling can be performed by rotational cooling, coil cooling, forced air cooling, water cooling, water mist cooling, emulsion cooling, any suitable cooling technique, or any combination thereof.
[0043] In other embodiments, the homogenization step is performed after casting in an in-line process or after cooling in an in-line process. In any in-line process, the cast aluminum alloy product, or a thermally stable cast aluminum alloy product, is passed through a tunnel furnace to homogenize the cast aluminum alloy product, or a thermally stable cast aluminum alloy product, at a homogenization temperature (i.e., peak metal temperature (PMT)) of approximately 400°C to approximately 520°C (e.g., approximately 410°C to approximately 510°C, approximately 420°C to approximately 500°C, approximately 422°C to approximately 520°C, approximately 400°C to approximately 500°C, or approximately 425°C to approximately 475°C). For example, the homogenization temperature can be approximately 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, or 520°C. In some cases, a homogenization process is used to maintain a uniform temperature in a cast aluminum alloy product, or a thermally stable cast aluminum alloy product. For example, if cooling can occur faster at the edges of a cast aluminum alloy product than at the center, a nearly cast aluminum alloy product may cool unevenly. A uniformly cooled cast aluminum alloy product can be obtained by passing the cast aluminum alloy product, or a thermally stable cast aluminum alloy product, through a tunnel furnace after casting or after cooling.
[0044] In some embodiments, a reheating step is performed to prepare a cast aluminum alloy product, or a thermally stable cast aluminum alloy product, for the subsequent hot rolling step. The reheating step can be performed as an in-line process (i.e., in a tunnel furnace) or as an offline process (for example, a coil cast aluminum alloy product, or a thermally stable coil cast aluminum alloy product, can be reheated in a box furnace before hot rolling). In some cases, reheating is performed by heating the cast aluminum alloy product, or a thermally stable cast aluminum alloy product, to the hot rolling temperature described below.
[0045] Hot rolling A hot rolling process can be carried out after the casting process. In some cases, the hot rolling process can be carried out immediately after casting. The hot rolling process may include hot inversion milling and / or hot tandem milling. The hot rolling process can be carried out at a hot rolling temperature (e.g., hot rolling inlet temperature) in the range of about 250°C to about 500°C (e.g., about 300°C to about 400°C, or about 350°C to about 430°C). For example, the hot rolling process can be carried out at a hot rolling temperature of approximately 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, or any point in between.
[0046] In the hot rolling process, cast aluminum alloy products can be hot-rolled to a thickness of 15 mm or less (for example, about 2 mm to about 10 mm) to provide aluminum alloy hot bands. For example, cast aluminum alloy products can be hot-rolled to a gauge of about 15 mm or less, 14 mm or less, 13 mm or less, 12 mm or less, 11 mm or less, 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, or 0.5 mm gauge. In some cases, the reduction in thickness obtained by the hot rolling process can be at least about 30% (for example, about 30% to about 50%). For example, the thickness of a cast aluminum alloy product can be reduced by approximately 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%. In some cases, an aluminum alloy hot band can exit a hot invert mill and / or hot tandem mill (i.e., a hot mill) at a temperature of approximately 300°C to 400°C. For example, an aluminum alloy hot band can have a hot mill exit temperature of approximately 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or any point in between.
[0047] Coiling and coil cooling Optionally, the aluminum alloy hot band can be wound into a hot band coil as it exits the hot mill. In some further embodiments, the hot band coil is cooled in air (referred to as coil cooling). The coil cooling process can be carried out at a rate of approximately 12.5°C / hour (°C / h) to approximately 3600°C / h. For example, the coil cooling process can be carried out at a rate of approximately 12.5°C / h, approximately 25°C / h, approximately 50°C / h, approximately 100°C / h, approximately 200°C / h, approximately 400°C / h, approximately 800°C / h, approximately 1600°C / h, approximately 3200°C / h, approximately 3600°C / h, or any point in between. The hot band coil can be cooled to a temperature of approximately 200°C to approximately 400°C. For example, a hot band coil can be cooled to temperatures of approximately 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, or 400°C.
[0048] In some embodiments, the air-cooled coil can be stored for a certain period of time. For example, the coil can be maintained at a temperature of approximately 200°C to approximately 400°C for more than one hour (e.g., more than two hours, more than five hours, more than ten hours, more than one day, more than two days, or more than one week).
[0049] Optional processing steps: homogenization, hot rolling to final gauge, coil cooling, and cold rolling to final gauge Optionally, homogenization can be performed after hot rolling, coiling, and coil cooling. The homogenization step may include heating the hot band coil to obtain a peak metal temperature (PMT) of approximately, or at least approximately 450°C (e.g., at least approximately 460°C, at least approximately 470°C, at least approximately 480°C, at least approximately 490°C, at least approximately 500°C, at least approximately 510°C, at least approximately 520°C, at least approximately 530°C, at least approximately 540°C, at least approximately 550°C, at least approximately 560°C, at least approximately 570°C, or at least approximately 580°C). For example, the hot band coil can be heated to a homogenization temperature of approximately 450°C to approximately 580°C, approximately 460°C to approximately 575°C, approximately 465°C to approximately 570°C, approximately 470°C to approximately 565°C, approximately 475°C to approximately 555°C, or approximately 480°C to approximately 550°C. In some cases, the heating rate relative to the homogenization temperature / PMT can be approximately 100°C / hour or less, approximately 75°C / hour or less, approximately 50°C / hour or less, approximately 40°C / hour or less, approximately 30°C / hour or less, approximately 25°C / hour or less, approximately 20°C / hour or less, or approximately 15°C / hour or less. In other cases, the heating rate relative to the homogenization temperature / PMT can be approximately 10°C / min to approximately 100°C / min (for example, approximately 10°C / min to approximately 90°C / min, approximately 15°C / min to approximately 70°C / min, approximately 20°C / min to approximately 60°C / min, approximately 20°C / min to approximately 50°C / min, or approximately 30°C / min to approximately 40°C / min).
[0050] Next, the hotband coil is immersed for a certain period of time (i.e., held at the indicated temperature). According to a non-limiting example, the hotband coil may be immersed for a maximum of approximately 36 hours (e.g., approximately 30 minutes, approximately 2 hours, or approximately 36 hours). For example, the hotband coil may be immersed for the indicated times of 30 minutes, 60 minutes (i.e., 1 hour), 90 minutes, 120 minutes (i.e., 2 hours), 150 minutes, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours, 30 hours, 31 hours, 32 hours, 33 hours, 34 hours, 35 hours, 36 hours, or any point in between.
[0051] In some non-limiting cases, the homogenization process is not performed.
[0052] Optionally, the homogenized hot band coil can be hot-rolled to produce a final gauge aluminum alloy product. Hot rolling to the final gauge process can be carried out after the homogenization process, for example, using a finishing mill. The hot rolling process can be carried out at a hot rolling temperature in the range of approximately 250°C to approximately 500°C (e.g., approximately 300°C to approximately 400°C, or approximately 350°C to approximately 430°C). For example, the hot rolling process can be carried out at a hot rolling temperature of approximately 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, or any point in between.
[0053] Hot rolling to the final gauging process can further reduce the thickness of the hot band to a final gauge of approximately 0.5 mm to 6 mm. For example, hot rolling to the final gauging process can yield aluminum alloy products with gauges of approximately 6 mm or less, approximately 5.5 mm or less, approximately 5 mm or less, approximately 4.5 mm or less, approximately 4 mm or less, approximately 3.5 mm or less, approximately 3 mm or less, approximately 2.5 mm or less, approximately 2 mm or less, approximately 1.5 mm or less, approximately 1 mm or less, approximately 0.5 mm, or any location in between.
[0054] Optionally, after homogenization, the homogenized hot band coil can undergo coil cooling and cold rolling. The homogenized hot band coil can be cooled in air at a rate of approximately 12.5°C / hour (°C / h) to approximately 3600°C / h. For example, the coil cooling process can be carried out at a rate of approximately 12.5°C / h, approximately 25°C / h, approximately 50°C / h, approximately 100°C / h, approximately 200°C / h, approximately 400°C / h, approximately 800°C / h, approximately 1600°C / h, approximately 3200°C / h, approximately 3600°C / h, or any point in between. After coil cooling, a cold rolling process can optionally be carried out. During the cold rolling process, the homogenized hot band coil can be cold-rolled to a thickness of approximately 0.1 mm to approximately 6 mm (for example, approximately 0.5 mm to approximately 5 mm). For example, a homogenized hot-band coil can be cold-rolled to a thickness of less than approximately 4 mm to produce a final gauge aluminum alloy product. For example, the final gauge aluminum alloy product may have a thickness of approximately 6 mm or less, approximately 5.5 mm or less, approximately 5 mm or less, approximately 4.5 mm or less, approximately 4 mm or less, approximately 3.5 mm or less, approximately 3 mm or less, approximately 2.5 mm or less, approximately 2 mm or less, approximately 1.5 mm or less, approximately 1 mm or less, approximately 0.5 mm, or any location in between. Optionally, the cold-rolling process can be carried out without the homogenization and / or hot-rolling processes.
[0055] In some cases, an exemplary sequence of steps used to further process a hot band coil to obtain a final gauge aluminum alloy product includes homogenizing the hot band coil to provide a homogenized hot band coil, and hot-rolling the homogenized hot band coil to provide a final gauge aluminum alloy product. In other cases, an exemplary sequence of steps used to further process a hot band coil to obtain a final gauge aluminum alloy product includes homogenizing the hot band coil to provide a homogenized hot band coil, cooling the homogenized hot band coil, and cold-rolling the homogenized hot band coil to provide a final gauge aluminum alloy product. In yet other cases, further processing a hot band coil to provide a final gauge aluminum alloy product includes cold-rolling the hot band coil to provide a final gauge aluminum alloy product. In some embodiments, further processing a hot band coil to provide a final gauge aluminum alloy product includes coil cooling, cold-rolling to final gauge, solution treatment, paint baking, and aging.
[0056] solution treatment The methods described herein further include a step of solution-thermalizing the final gauge aluminum alloy product. The solution-thermal step may optionally include heating or cooling the final gauge aluminum alloy product to a solution temperature of about 450°C or higher (e.g., about 460°C to about 600°C, about 465°C to about 575°C, about 470°C to about 550°C, about 475°C to about 525°C, or about 480°C to about 500°C). The final gauge aluminum alloy product may be immersed at the solution temperature for a certain period of time. In certain embodiments, the final gauge aluminum alloy product is immersed for at least 30 seconds (e.g., about 60 seconds to about 120 seconds: including these values). For example, the final gauge aluminum alloy product may be immersed at a temperature of approximately 450°C or higher for 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 110 seconds, 115 seconds, 120 seconds, 125 seconds, 130 seconds, 135 seconds, 140 seconds, 145 seconds, 150 seconds, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes, 90 minutes, 95 minutes, 100 minutes, 105 minutes, 110 minutes, 115 minutes, or 120 minutes, or any point in between. In certain embodiments, solution treatment is performed immediately after the hot rolling or cold rolling process.
[0057] Hardening The methods described herein include a quenching step. As used herein, the term “quenching” may include rapidly lowering the temperature of the final gauge aluminum alloy product that has been dissolved as described above. In the quenching step, the product may be quenched with a liquid (e.g., water), a gas, any other suitable quenching medium, or any combination thereof. In certain embodiments, the product may be quenched with water having a water temperature of about 40°C to about 75°C. In certain embodiments, the product may be quenched with forced air.
[0058] In a particular embodiment, the manufactured product can be cooled to a temperature of approximately 25°C to approximately 65°C in a quenching process based on a selected gauge, with a quenching rate that can vary between approximately 50°C / s and 400°C / s. For example, the quenching rate can be approximately 50°C / s to approximately 375°C / s, approximately 60°C / s to approximately 375°C / s, approximately 70°C / s to approximately 350°C / s, approximately 80°C / s to approximately 325°C / s, approximately 90°C / s to approximately 300°C / s, approximately 100°C / s to approximately 275°C / s, approximately 125°C / s to approximately 250°C / s, approximately 150°C / s to approximately 225°C / s, or approximately 175°C / s to approximately 200°C / s.
[0059] Pre-aging In some cases, a pre-aging process can be performed. While not theoretically bound, a pre-aging process at least partially prevents the changes in mechanical properties caused by the natural aging of the aluminum alloy product. Optionally, a pre-aging process can be performed before or after the solution treatment process. The pre-aging process may include heating the final gauge aluminum alloy product to a pre-aging temperature of approximately 50°C to 150°C (e.g., approximately 55°C to 140°C, 60°C to 130°C, 65°C to 120°C, or 70°C to 110°C). For example, the pre-aging process may include heating the final gauge aluminum alloy product to a temperature of approximately 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C. The final gauge aluminum alloy product can be maintained at the pre-aging temperature for a period of up to approximately 24 hours (e.g., approximately 1 hour to approximately 24 hours). For example, the final gauge aluminum alloy product can be maintained for approximately 24 hours or less, approximately 12 hours or less, approximately 6 hours or less, approximately 5 hours or less, approximately 4 hours or less, approximately 3 hours or less, approximately 2 hours or less, approximately 1 hour or less, or any point in between.
[0060] Aging After solution treatment, a quenching and / or pre-aging process, and one or more aging processes may be carried out. Aging may include one or more of the following: natural aging, artificial aging, paint baking, and post-formation heat treatment.
[0061] Optionally, aging may include a natural aging process. Natural aging may include a process of maintaining the final gauge aluminum alloy product at room temperature for a certain period of time. For example, the final gauge aluminum alloy product can be maintained at room temperature for up to approximately 12 weeks (e.g., approximately 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, 1 week, 2 weeks, 3 weeks, 4 weeks, 5 weeks, 6 weeks, 7 weeks, 8 weeks, 9 weeks, 10 weeks, 11 weeks, or 12 weeks).
[0062] Aluminum alloy products prepared according to the methods described herein may be delivered after any pre-aging and natural aging. High yield strength can be achieved after end-user processing, for example, by deformation (e.g., stamping, pressure forming, molding, or any suitable deformation process) and / or by aging or heat treatment (e.g., coating and paint baking, artificial aging, post-forming heat treatment, or any suitable end-user heat treatment). Optionally, after any pre-aging and / or natural aging process, the aluminum alloy products described herein may be subjected to, for example, a molding process, a coating process, an artificial aging process, and / or a paint baking process.
[0063] Optionally, aging may include an artificial aging process. Artificial aging may include heating the final gauge aluminum alloy product to an artificial aging temperature of approximately 100°C to approximately 250°C (e.g., approximately 110°C to approximately 220°C, approximately 115°C to approximately 210°C, or approximately 125°C to approximately 200°C). The artificial aging process may include maintaining the artificial aging temperature for a period of approximately 1 hour to approximately 72 hours (e.g., approximately 1 hour, approximately 2 hours, approximately 3 hours, approximately 4 hours, approximately 5 hours, approximately 6 hours, approximately 7 hours, approximately 8 hours, approximately 9 hours, approximately 10 hours, approximately 11 hours, approximately 12 hours, approximately 24 hours, approximately 48 hours, approximately 60 hours, or approximately 72 hours).
[0064] In some embodiments, any coating procedure (e.g., painting, electrocoating, or zinc phosphate treatment, to name a couple of examples) can be performed. After coating, the final gauge aluminum alloy product can be subjected to further heat treatment, including paint baking, post-forming heat treatment, any suitable OEM heat treatment process, or any combination thereof. Paint baking can further strengthen the aluminum alloy product to provide a high-strength aluminum alloy product with optionally complex formed surfaces. In some cases, the paint baking procedure may include heating the aluminum alloy product to a paint baking temperature of about 75°C to about 250°C and maintaining the aluminum alloy product at the paint baking temperature for a period of up to about 3 hours (e.g., about 15 minutes to 2 hours, or about 30 minutes to about 1 hour). In some further cases, post-forming heat treatment can be performed. The post-forming heat treatment procedure may include heating the final gauge aluminum alloy product to a post-forming heat treatment temperature of approximately 100°C to 250°C and maintaining this temperature for approximately 1 hour to 24 hours (for example, approximately 2 hours to 12 hours).
[0065] Characteristics of alloy products The aluminum alloy products described herein may possess high strength and formability before and after the aging process described herein. Tensile testing of samples shall be performed according to standard procedures known in the field of materials science, as described in relevant publications, such as those provided by the American Society for Testing and Materials (ASTM). ASTM E8 / EM8 (DOI:10.1520 / E0008 E0008M-15A), titled "Standard Test Procedures for Tensile Testing of Metallic Materials," specifies the tensile testing procedure for metallic materials.
[0066] In some cases, aluminum alloy products achieve increased elongation and yield strength after aging compared to the elongation and yield strength achieved by the aluminum alloy product before aging. The increase in elongation can be at least about 1% (e.g., about 1.5% to about 5%, or about 2% to about 3%). For example, the increase in elongation can be about 1%, about 1.5%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 4.5%, about 5%, or more than about 5%. The increase in yield strength can be at least about 15 MPa (e.g., about 15 MPa to about 25 MPa). For example, the increase in yield strength can be about 15 MPa, about 16 MPa, about 17 MPa, about 18 MPa, about 19 MPa, about 20 MPa, about 21 MPa, about 22 MPa, about 23 MPa, about 24 MPa, about 25 MPa, or more than about 25 MPa.
[0067] In some embodiments, aluminum alloy products provided in grade T6 have a yield strength of more than about 400 MPa after treatment according to the method described herein. For example, an aluminum alloy product, after treatment according to the method described herein, may have a yield strength of 400 MPa or more, 405 MPa or more, 410 MPa or more, 415 MPa or more, 420 MPa or more, 425 MPa or more, 430 MPa or more, 435 MPa or more, 440 MPa or more, 445 MPa or more, 450 MPa or more, 455 MPa or more, 460 MPa or more, 465 MPa or more, 470 MPa or more, 475 MPa or more, 480 MPa or more, 485 MPa or more, 490 MPa or more, 495 MPa or more, 500 MPa or more, 505 MPa or more, 510 MPa or more, 515 MPa or more, 520 MPa or more, 525 MPa or more, 530 MPa or more, 535 MPa or more, 540 MPa or more, 545 MPa or more, 550 MPa or more, 555 MPa or more, 560 MPa or more, 565 MPa or more, 570 MPa or more, or 575 MPa or more.
[0068] In some cases, aluminum alloy products provided in grade T4 have a yield strength of more than about 240 MPa after processing according to the method described herein. For example, aluminum alloy products may have a yield strength of about 240 MPa or more, about 250 MPa or more, about 260 MPa or more, about 270 MPa or more, about 280 MPa or more, about 290 MPa or more, about 300 MPa or more, about 310 MPa or more, about 320 MPa or more, about 330 MPa or more, about 340 MPa or more, about 350 MPa or more, about 360 MPa or more, about 370 MPa or more, about 380 MPa or more, about 390 MPa or more, about 400 MPa or more, about 410 MPa or more, about 420 MPa or more, or about 425 MPa or more.
[0069] In some embodiments, the aluminum alloy product, when provided in a T6 temper class after processing according to the method described herein, has a uniform elongation of more than about 6%.For example, aluminum alloy products of quality T6 are distributed as follows: approximately 6%, approximately 6.1%, approximately 6.2%, approximately 6.3%, approximately 6.4%, approximately 6.5%, approximately 6.6%, approximately 6.7%, approximately 6.8%, approximately 6.9%, approximately 7%, approximately 7.1%, approximately 7.2%, approximately 7.3%, approximately 7.4%, approximately 7.5%, approximately 7.6%, approximately 7.7%, approximately 7.8%, approximately 7.9%, approximately 8%, approximately 8.1%, approximately 8.2%, approximately 8.3%, approximately 8.4%, approximately 8.5%, approximately 8.6%, approximately 8.7%, approximately 8.8%, approximately 8.9%, approximately 9%, approximately 9.1%, approximately 9.2%, approximately 9.3%, approximately 9.4%, approximately 9.5%, approximately 9.6%, and approximately 9. 0.7%, approximately 9.8%, approximately 9.9%, approximately 10%, approximately 10.1%, approximately 10.2%, approximately 10.3%, approximately 10.4%, approximately 10.5%, approximately 10.6%, approximately 10.7%, approximately 10.8%, approximately 10.9%, approximately 11%, approximately 11.1%, approximately 11.2%, approximately 11.3%, approximately 11.4%, approximately 11.5%, approximately 11.6%, approximately 11.7%, approximately 11.8%, approximately 11.9%, approximately 12%, approximately 12.1%, approximately 12.2%, approximately 12.3%, approximately 12.4%, approximately 12.5%, approximately 12.6%, approximately 12.7%, approximately 12.8%, approximately 12.9%, approximately 13%, approximately 13.1%, approximately 13.2%, approximately 13.3%, approximately 13.4%, approximately 13.5%, approximately 13.6%, approximately 13.7%, approximately 13.8%, approximately 13.9%, approximately 14%, approximately 14.1%, approximately 14.2%, approximately 14.3%, approximately 14.4%, approximately 14.5%, approximately 14.6%, approximately 14.7%, approximately 14.8%, approximately 14.9%, approximately 15%, approximately 15.1%, approximately 15.2%, approximately 15.3%, approximately 15.4%, approximately 15.5%, approximately 15.6%, approximately 15.7%, approximately 15.8%, approximately 15.9%, approximately 16%, approximately 16.1%, approximately 16.2%, approximately 16.3%, approximately 16.4%, approximately 16.5%, approximately 16.6%, approximately 16.7%, approximately It can have a uniform elongation of 16.8%, approximately 16.9%, approximately 17%, approximately 17.1%, approximately 17.2%, approximately 17.3%, approximately 17.4%, approximately 17.5%, approximately 17.6%, approximately 17.7%, approximately 17.8%, approximately 17.9%, approximately 18%, approximately 18.1%, approximately 18.2%, approximately 18.3%, approximately 18.4%, approximately 18.5%, approximately 18.6%, approximately 18.7%, approximately 18.8%, approximately 18.9%, approximately 19%, approximately 19.1%, approximately 19.2%, approximately 19.3%, approximately 19.4%, approximately 19.5%, approximately 19.6%, approximately 19.7%, approximately 19.8%, approximately 19.9%, or approximately 20%.
[0070] In some embodiments, the aluminum alloy product has a uniform elongation of more than about 16% when provided in a T4 quality after processing according to the method described herein.For example, aluminum alloy products of quality T4 are approximately 16%, 16.1%, 16.2%, 16.3%, 16.4%, 16.5%, 16.6%, 16.7%, 16.8%, 16.9%, 17%, 17.1%, 17.2%, 17.3%, 17.4%, 17.5%, 17.6%, 17.7%, 17.8%, 17.9%, 18%, 18.1%, 18.2%, 18.3%, 18.4%, 18.5%, 18.6%, 18.7%, 18.8%, 18.9%, 19%, 19.1%, 19.2%, and 19%. 0.3%, approximately 19.4%, approximately 19.5%, approximately 19.6%, approximately 19.7%, approximately 19.8%, approximately 19.9%, approximately 20%, approximately 20.1%, approximately 20.2%, approximately 20.3%, approximately 20.4%, approximately 20.5%, approximately 20.6%, approximately 20.7%, approximately 20.8%, approximately 20.9%, approximately 21%, approximately 21.1% Approximately 21.2%, 21.3%, 21.4%, 21.5%, 21.6%, 21.7%, 21.8%, 21.9%, 22%, 22.1%, 22.2%, 22.3%, 22.4%, 22.5%, 22.6%, 22.7%, 22.8%, 22.9%, Approximately 23%, approximately 23.1%, approximately 23.2%, approximately 23.3%, approximately 23.4%, approximately 23.5%, approximately 23.6%, approximately 23.7%, approximately 23.8%, approximately 23.9%, approximately 24%, approximately 24.1%, approximately 24.2%, approximately 24.3%, approximately 24.4%, approximately 24.5%, approximately 24.6%, approximately 24.7%, approximately 2 4.8%, approximately 24.9%, approximately 25%, approximately 25.1%, approximately 25.2%, approximately 25.3%, approximately 25.4%, approximately 25.5%, approximately 25.6%, approximately 25.7%, approximately 25.8%, approximately 25.9%, approximately 26%, approximately 26.1%, approximately 26.2%, approximately 26.3%, approximately 26.4%, approximately 26.5%, approximately 26.6% It can have a uniform elongation of approximately 26.7%, 26.8%, 26.9%, 27%, 27.1%, 27.2%, 27.3%, 27.4%, 27.5%, 27.6%, 27.7%, 27.8%, 27.9%, 28%, 28.1%, 28.2%, 28.3%, 28.4%, 28.5%, 28.6%, 28.7%, 28.8%, 28.9%, 29%, 29.1%, 29.2%, 29.3%, 29.4%, 29.5%, 29.6%, 29.7%, 29.8%, 29.9%, or approximately 30%.
[0071] The aluminum alloy products described herein can have excellent bending properties before and after the aging process described herein. Aluminum alloy products prepared according to the methods described herein exhibit the desired bending properties when measured by a three-point bending test in accordance with ISO 7438 (general bending standard) and VDA 238-100. For example, the aluminum alloy products can have a VDAα bending angle greater than approximately 65°. In some cases, aluminum alloy products have angles of approximately 65°, 65.1°, 65.2°, 65.3°, 65.4°, 65.5°, 65.6°, 65.7°, 65.8°, 65.9°, 66°, 66.1°, 66.2°, 66.3°, 66.4°, 66.5°, 66.6°, 66.7°, 66.8°, 66.9°, 67°, 67.1°, 67.2°, 67.3°, 67.4°, 67.5°, and 67. 6°, approximately 67.7°, approximately 67.8°, approximately 67.9°, approximately 68°, approximately 68.1°, approximately 68.2°, approximately 68.3°, approximately 68.4°, approximately 68.5°, approximately 68.6°, approximately 68.7°, approximately 68.8°, approximately 68.9°, approximately 69°, approximately 69.1°, approximately 69.2°, approximately 69.3°, approximately 69.4°, approximately 69.5°, approximately 69.6°, approximately 69.7°, approximately 69.8°, approximately 69.9°, approximately 70°, approximately 70.1°, approximately 70.2°, approximately 70.3°, approximately 70.4°, approximately 70.5°, approximately 7 0.6°, approximately 70.7°, approximately 70.8°, approximately 70.9°, approximately 71°, approximately 71.1°, approximately 71.2°, approximately 71.3°, approximately 71.4°, approximately 71.5°, approximately 71.6°, approximately 71.7°, approximately 71.8°, approximately 71.9°, approximately 72°, approximately 72.1°, approximately 72.2°, approximately 72.3°, approximately 72.4°, approximately 72.5°, approximately 72.6°, approximately 72.7°, approximately 72.8°, approximately 72.9°, approximately 73°, approximately 73.1°, approximately 73.2°, approximately 73.3°, approximately 73.4°, approximately 73.5° Approximately 73.6°, 73.7°, 73.8°, 73.9°, 74°, 74.1°, 74.2°, 74.3°, 74.4°, 74.5°, 74.6°, 74.7°, 74.8°, 74.9°, 75°, 75.1°, 75.2°, 75.3°, 75.4°, 75.5°, 75.6°, 75.7°, 75.8°, 75.9°, 76°, 76.1°, 76.2°, 76.3°, 76.4°, 76.5°, approximately 76.6°, approximately 76.7°, approximately 76.8°, approximately 76.9°, approximately 77°, approximately 77.1°, approximately 77.2°, approximately 77.3°, approximately 77.4°, approximately 77.5°, approximately 77.6°, approximately 77.7°, approximately 77.8°, approximately 77.9°, approximately 78°, approximately 78.1°, approximately 78.2°, approximately 78.3°, approximately 78.4°, approximately 78.5°, approximately 78.6°, approximately 78.7°, approximately 78.8°, approximately 78.9°, approximately 79°, approximately 79.1°, approximately 79.2°, approximately 79.3°, approximately 79.4°, approximately 79.5°, approximately 79.6°, approximately 79.7°, approximately 79.8°, approximately 79.9°, Approximately 80°, 80.1°, 80.2°, 80.3°, 80.4°, 80.5°, 80.6°, 80.7°, 80.8°, 80.9°, 81°, 81.1°, 81.2°, 81.3°, 81.4°, 81.5°, 81.6°, 81.7°, 81.8°, 81.9°, 82°, 82.1°, 82.2°, 82.3°, 82.4°, 82.5°, 82.6°, 82.7°, 82.8°, 82.9°, 83°, 83.1°, 83.2°, 83.3°, 83.4° Approximately 83.5°, 83.6°, 83.7°, 83.8°, 83.9°, 84°, 84.1°, 84.2°, 84.3°, 84.4°, 84.5°, 84.6°, 84.7°, 84.8°, 84.9°, 85°, 85.1°, 85.2°, 85.3°, 85.4°, 85.5°, 85.6°, 85.7°, 85.8°, 85.9°, 86°, 86.1°, 86.2°, 86.3°, 86.4°, 86.5°, 86.6°, 86.7°, 86.8°, 8 The VDAα can have a bending angle of approximately 6.9°, 87°, 87.1°, 87.2°, 87.3°, 87.4°, 87.5°, 87.6°, 87.7°, 87.8°, 87.9°, 88°, 88.1°, 88.2°, 88.3°, 88.4°, 88.5°, 88.6°, 88.7°, 88.8°, 88.9°, 89°, 89.1°, 89.2°, 89.3°, 89.4°, 89.5°, 89.6°, 89.7°, 89.8°, 89.9°, or approximately 90°.
[0072] How to use The alloy products and methods described herein can be used in automotive and / or transportation applications, including automobile, aircraft, and rail applications, or in any other desired applications. In some embodiments, the products and methods can be used to produce automotive body parts, such as bumpers, side beams, roof beams, cross beams, pillar reinforcements (e.g., A-pillars, B-pillars, and C-pillars), interior panels, exterior panels, side panels, interior hoods, exterior hoods, or trunk lid panels. The aluminum alloy products and methods described herein can also be used in aircraft or rail vehicle applications, for example, to produce exterior and interior panels.
[0073] The products and methods described herein may also be used for electronic applications, for example, to create external and internal enclosures. For example, the products and methods described herein may also be used to create enclosures for electronic devices, including mobile phones and tablet computers. In some embodiments, the products may be used to create enclosures for the external casing of the bottom chassis of mobile phones (e.g., smartphones) and tablets.
[0074] In certain embodiments, the articles and methods may be used to manufacture aerospace vehicle component products. For example, the disclosed articles and methods may be used to manufacture aircraft body components, such as skin alloys. The articles and methods may be used in any other desired applications.
[0075] Examples Example 1 is a method for producing a formable high-strength aluminum alloy product, the method comprising: continuously casting a molten aluminum alloy composition to provide a cast aluminum alloy product having a casting outlet temperature, wherein the molten aluminum alloy composition comprises at least 0.1% by weight of Zr, at least 2% by weight of Mg, and an aluminum alloy containing Zn as a major alloying element other than Al; cooling the cast aluminum alloy product to a temperature 20°C to 50°C below the casting outlet temperature to provide a heat-stabilized cast aluminum alloy product; hot rolling the heat-stabilized cast aluminum alloy product to provide an aluminum alloy hot band; coiling the aluminum alloy hot band to provide a hot band coil; cooling the hot band coil to a temperature 200°C to 400°C; further processing the hot band coil to provide a final gauge aluminum alloy product; and solution treatment of the final gauge aluminum alloy product.
[0076] Example 2 is a method according to either the preceding or succeeding example, wherein the molten aluminum alloy composition contains a Zn-to-Mg ratio of about 1.2 to about 3.
[0077] Example 3 is a method according to either a prior or subsequent example, wherein the hot rolling process includes heating a heat-stabilized cast aluminum alloy product to the hot rolling inlet temperature.
[0078] Example 4 is a method according to either the preceding or succeeding example, wherein a heat-stabilized cast aluminum alloy product is hot-rolled to reduce the thickness of the heat-stabilized cast aluminum alloy product by at least 30%.
[0079] Example 5 is a method used in either the preceding or succeeding example, which reduces the thickness of a cast aluminum alloy product by 40% to 50%.
[0080] Example 6 is a method of either the preceding or succeeding example, wherein further processing includes homogenizing the hot band coil to provide a homogenized hot band coil, and hot rolling the homogenized hot band coil to provide a final gauge aluminum alloy product.
[0081] Example 7 is a method of either the preceding or succeeding example, wherein further processing includes homogenizing the hot band coil to provide a homogenized hot band coil, cooling the homogenized hot band coil, and cold rolling the homogenized hot band coil to provide a final gauge aluminum alloy product.
[0082] Example 8 is a method according to either a prior or subsequent example, wherein homogenization includes heating an aluminum alloy hot band to a homogenization temperature of at least 450°C and maintaining the aluminum alloy hot band at a homogenization temperature of at least 450°C for a period of at least about 90 minutes.
[0083] Example 9 is a method of either the preceding or succeeding example, wherein further processing includes cold rolling of the hot-banded coil to provide a final gauge aluminum alloy product.
[0084] Example 10 further includes pre-aging of a final gauge aluminum alloy product, wherein the pre-aging comprises heating the final gauge aluminum alloy product to a pre-aging temperature of approximately 50°C to approximately 150°C and maintaining the pre-aging temperature for a period of approximately 1 hour to approximately 24 hours, as described in either the preceding or succeeding example.
[0085] Example 11 is a method of either a prior or subsequent example, further comprising aging the final gauge aluminum alloy product to achieve a yield strength of at least 400 MPa.
[0086] Example 12 is a method of either a preceding or succeeding example in which aging includes one or more of the following: natural aging, artificial aging, paint baking, and post-molding heat treatment.
[0087] Example 13 is a method of either a preceding or succeeding example, wherein aging includes natural aging, which involves maintaining the final gauge aluminum alloy product at room temperature for a period of approximately 1 day to approximately 12 weeks.
[0088] Example 14 is a method according to either a prior or subsequent example, wherein aging includes artificial aging, and artificial aging includes heating the final gauge aluminum alloy product to an artificial aging temperature of approximately 100°C to approximately 250°C, and maintaining the artificial aging temperature for a period of approximately 1 hour to approximately 72 hours.
[0089] Example 15 is a method of either a prior or subsequent example, wherein aging includes paint baking, and paint baking includes heating the final gauge aluminum alloy product to a paint baking temperature of approximately 75°C to approximately 250°C and maintaining the paint baking temperature for a period of approximately 15 minutes to approximately 3 hours.
[0090] Example 16 is a method according to either a prior or subsequent example, wherein the aging includes a post-forming heat treatment, and the post-forming heat treatment includes heating the final gauge aluminum alloy product to a post-forming heat treatment temperature of approximately 100°C to approximately 250°C, and maintaining the post-forming heat treatment temperature for a period of approximately 1 hour to approximately 24 hours.
[0091] Example 17 is an aluminum alloy product prepared according to the method described in either the preceding or subsequent example.
[0092] Example 18 is an aluminum alloy product described in either the preceding or succeeding example, wherein the aluminum alloy product achieves increased elongation and increased yield strength after aging.
[0093] Example 19 is an aluminum alloy product described in either the preceding or succeeding example, wherein the increase in elongation is at least about 1%.
[0094] Example 20 is an aluminum alloy product described in either the preceding or succeeding example, with an increase in elongation of approximately 1.5% to 5%.
[0095] Example 21 is an aluminum alloy product described in either the preceding or succeeding example, wherein the increase in yield strength is at least about 15 MPa.
[0096] Example 22 is an aluminum alloy product described in either the preceding or succeeding example, with a yield strength increase of approximately 15 MPa to approximately 25 MPa.
[0097] Example 23 is an aluminum alloy product described in any of the prior examples, wherein the increase in elongation is at least about 1% and the increase in yield strength is at least about 15 MPa.
[0098] The following examples are helpful in further illustrating the present invention, but do not constitute any limitation thereof. Rather, it should be clearly understood that various embodiments, modifications, and equivalents can be relied upon, and these may be suggested to those skilled in the art without departing from the spirit of the invention after reading this specification. [Examples]
[0099] Example 1: Preparation and manufacturing method of highly formable, high-strength aluminum alloy The aluminum alloy processing methods described herein include hot rolling, coil cooling, homogenization, hot rolling to a final gauge, and solution treatment (referred to herein as "Route 1"). Figure 1A is a schematic diagram representing processing method 100 of Route 1. An aluminum alloy slab 120 was produced using a continuous casting machine 110. The aluminum alloy slab 120 exited the continuous casting machine 110 at a temperature of approximately 400°C to approximately 430°C. Next, the aluminum alloy slab 120 was processed in a hot mill 130 to reduce the thickness of the aluminum alloy slab 120 by approximately 40% to approximately 50% to produce a hot band 125. Next, the hot band 125 was coiled at a temperature of approximately 350°C, and then the coil 140 was subjected to further processing. The coil 140 was subsequently homogenized in a box furnace 150 at a homogenization temperature of approximately 480°C for approximately 2 hours. After homogenization, the coil 140 was unwound, and the hot band 125 was further hot-rolled in a finishing mill 160 to produce the final gauge aluminum alloy product 127. Next, the final gauge aluminum alloy product 127 was coiled, and then the aluminum alloy product coil 170 was subjected to a solution treatment process. In some cases, the aluminum alloy product coil was subjected to a pre-aging process before the solution treatment process. In some embodiments, the aluminum alloy product coil was subjected to other aging processes after the solution treatment process.
[0100] Another aluminum alloy processing method described herein includes hot rolling, coil cooling, homogenization, coil cooling, cold rolling, and solution treatment (referred herein to as "Route 2"). Figure 1B is a schematic diagram representing processing method 101 of Route 2. Casting, hot rolling, coiling, coil cooling, and homogenization were carried out as described above. After homogenization, the coil 140 was unwound, and the hot band 125 was cold-rolled in a cold mill 165 to produce a final gauge aluminum alloy product 127. Next, the final gauge aluminum alloy product 127 was coiled, and the aluminum alloy product coil 170 was subjected to a solution treatment process. In some cases, the aluminum alloy product coil was subjected to a pre-aging process or other aging process.
[0101] Another aluminum alloy processing method described herein includes hot rolling, coil cooling, cold rolling, and solution treatment (referred herein to as "Route 3"). Figure 1C is a schematic diagram representing processing method 102 of Route 3. Casting, hot rolling, coiling, and coil cooling were carried out as described above to obtain coil 140. After coil cooling, coil 140 was unwound, and the hot band 125 was cold-rolled in a cold mill 165 to produce a final gauge aluminum alloy product 127. Next, the final gauge aluminum alloy product 127 was coiled, and then the aluminum alloy product coil 170 was subjected to a solution treatment process. In some cases, the aluminum alloy product coil 170 was subjected to a pre-aging process or other aging process.
[0102] Example 2: Mechanical properties of highly formable, high-strength aluminum alloy Cast aluminum alloy products were prepared using a continuous casting machine from an aluminum alloy composition (referred to herein as "Alloy A") containing 0.60 wt% Cu, 0.20 wt% Fe, 3.50 wt% Mg, 0.10 wt% Mn, 0.05 wt% Si, 0.02 wt% Ti, 0.10 wt% Cr, 4.50 wt% Zn, 0.12 wt% Zr, up to 0.15 wt% impurities, and the remainder being aluminum. Alloy A had a Zn / Mg ratio of approximately 1.3. Samples taken from Alloy A, prepared and fabricated according to the method described in Example 1, were subjected to mechanical testing. Routes 1, 2, and 3 (see Example 1) were all used with and without pre-aging. In some cases, an additional paint-baking step was used, in which the aluminum alloy product was heated to a temperature of approximately 180°C and maintained at this temperature for approximately 30 minutes.
[0103] Figure 2 is a summary graph showing the mechanical properties of alloy A prepared and treated according to the method described herein, with and without pre-aging ("no PX"), by heating the final gauge aluminum alloy product 127 to a temperature of approximately 70°C and maintaining this temperature for approximately 8 hours before solution treatment. After solution treatment, alloy A samples were naturally aged for one week. As shown in the graph, the yield strength of each sample (solid histogram on the left for each pair) ranged from approximately 280 MPa to approximately 325 MPa, regardless of the treatment route or whether pre-aging was used. The ultimate tensile strength (shaded histogram on the right for each pair) ranged from approximately 450 MPa to approximately 500 MPa for each aluminum alloy product sample. Uniform elongation (white circle) and total elongation (white diamond) ranged from approximately 17% to approximately 25% for each sample.
[0104] Figure 3 is a graph showing the mechanical properties of alloy A prepared and treated according to Route 1 ("HO-HRTG"), Route 2 ("HO-CC-CR"), and Route 3 ("CR") as described herein, without pre-aging and with one week of natural aging, to provide samples of temper T4 ("T4-1W"). Furthermore, artificial aging was performed by heating the samples to approximately 125°C and maintaining this temperature for 24 hours to create samples of temper T6 ("T6-1W"). The paint curing procedure described above was applied to specific samples (referred to as "T4+PB-1W" for the T4 sample and "T6+PB-1W" for the T6 sample). As shown in Figure 3, the yield strength of each sample (solid histogram on the left for each pair) increased significantly after artificial aging, regardless of the treatment path. The ultimate tensile strength (shaded histogram on the right for each pair) also increased in each aluminum alloy product sample. Uniform elongation (white circle) and total elongation (white diamond) decreased significantly in each sample.
[0105] Figure 4 is a graph showing the mechanical properties of alloy A prepared and treated according to Route 1 (referred to as "HO-HRTG"), Route 2 (referred to as "HO-CC-CR"), and Route 3 (referred to as "CR") as described herein, without pre-aging and with 4 weeks of natural aging, to provide samples of different tempers of T4 (referred to as "T4-4W"). Furthermore, artificial aging was performed by heating the samples to approximately 125°C and maintaining this temperature for 24 hours to prepare samples of different tempers of T6 (referred to as "T6-4W"). The paint curing procedure described above was applied to specific samples (referred to as "T4+PB-4W" for the T4 sample and "T6+PB-4W" for the T6 sample). As shown in Figure 4, the additional natural aging resulted in a slight increase in both yield strength (solid histogram on the left for each pair) and ultimate tensile strength (shaded histogram on the right for each pair). Surprisingly, formability (i.e., uniform elongation (white circle) and total elongation (white diamond)) increased significantly, indicating a high-strength and highly formable aluminum alloy.
[0106] Figure 5 is a graph showing the mechanical properties of alloy A prepared and treated according to Route 1 ("HO-HRTG"), Route 2 ("HO-CC-CR"), and Route 3 ("CR") as described herein, with pre-aging before solution treatment and one week of natural aging, to provide samples of different tempers of T4 ("T4-1W"). Furthermore, artificial aging was performed by heating the samples to approximately 125°C and maintaining this temperature for 24 hours to prepare samples of different tempers of T6 ("T6-1W"). The paint-baking procedure described above was applied to specific samples (referred to as "T4+PB-1W" for the T4 samples).
[0107] Figure 6 is a graph showing the mechanical properties of alloy A prepared and treated according to Route 1 ("HO-HRTG"), Route 2 ("HO-CC-CR"), and Route 3 ("CR") as described herein, with pre-aging before solution treatment and 4 weeks of natural aging, to provide samples of different tempers of T4 ("T4-4W"). Furthermore, samples of different tempers of T6 ("T6-4W") were prepared by artificial aging by heating the samples to approximately 125°C and maintaining this temperature for 24 hours. The paint baking procedure described above was applied to specific The process was applied to samples (referred to as "T4+PB-4W" for T4 samples and "T6+PB-4W" for T6 samples). As shown in Figures 5 and 6, pre-aging resulted in an increase of approximately 20 MPa in naturally aged samples after 1 week and 1 month of natural aging, both with and without paint baking. As shown in Figure 6, pre-aging surprisingly produced aluminum alloys of T4 temper with an increase of approximately 2% to 3% in formability compared to the aluminum alloy in the example in Figure 5 that underwent 1 week of natural aging, regardless of the treatment route.
[0108] The microstructure of alloy A samples prepared and fabricated according to Route 1, Route 2, and Route 3 was evaluated by optical microscopy. Particle size and distribution, as well as crystalline morphology, were analyzed. Figure 7 shows the particle size and distribution at the surface (referred to as "Surface," top row) and center (referred to as "Center," bottom row) of the aluminum alloy samples. Alloy A samples treated by Route 3 (cold rolling without homogenization, "CR") showed a large distribution of undissolved particles that could lead to cracking and fracture during the deformation process (e.g., forming). Alloy A samples treated by Routes 1 and 2 (e.g., with homogenization after the initial hot rolling) showed a microstructure free of precipitates, thus enabling improved formability.
[0109] Figure 8 shows the crystalline structure of the surface (referred to as "surface," top row) and the center (referred to as "center," bottom row) of the alloy A sample. The alloy A sample treated by Route 3 (cold rolling without homogenization, "CR") showed a finer crystalline structure than the sample treated with homogenization. The alloy A samples treated by Routes 1 and 2 (with homogenization after the initial hot rolling) showed a larger crystalline structure, which contributed to a yield strength approximately 20 MPa lower, as shown in the example in Figure 5.
[0110] Example 3: Preparation, fabrication, and aging method for highly formable, high-strength aluminum alloy The aluminum alloy processing methods described herein include homogenization, hot rolling, coil cooling, cold rolling to final gauge, solution treatment, paint baking, and aging (referred herein to as "Route 4"). Figure 9 is a schematic diagram representing processing method 900 of Route 4. An aluminum alloy slab 120 was produced using a continuous casting machine 110. The aluminum alloy slab 120 exited the continuous casting machine 110 at a temperature of approximately 400°C to approximately 430°C. The aluminum alloy slab 120 was homogenized using a tunnel furnace 905, and the temperature of the aluminum alloy slab 120 was maintained at a peak metal temperature of approximately 400°C to approximately 520°C for approximately 1 minute to approximately 5 minutes across the width of the aluminum alloy slab 120. Next, the aluminum alloy slab 120 was processed in a first finishing mill 910 to reduce its thickness by approximately 20% to 40%, and the slab was cooled to approximately 325°C to 375°C. Then, the aluminum alloy slab 120 was processed in a second finishing mill 920 to reduce its thickness by approximately 20% to 40%, and the slab was cooled to approximately 225°C to 275°C to produce a hot band 125. The hot band 125 was then coiled at a temperature of less than approximately 250°C, and the resulting coil 140 was then subjected to coil cooling. The coil 140 was then unwound, and the hot band 125 was further cold-rolled in a cold mill 165 to produce a final gauge aluminum alloy product 127. Next, the final gauge aluminum alloy product 127 was coiled to produce an aluminum alloy product coil 170. Next, the aluminum alloy coil 170 was subjected to solution treatment in a solution furnace 960 for approximately 2 to 5 minutes at a temperature of approximately 450°C to 500°C. After solution treatment, the aluminum alloy coil 170 was quenched to approximately room temperature by either water quenching or forced air quenching. In some cases, the aluminum alloy coil 170 was subjected to a pre-aging process before the solution treatment process. Optionally, the pre-aging process included aging at approximately 80°C for approximately 6 hours, or aging at approximately 100°C for approximately 2 hours.In some embodiments, the aluminum alloy coil 170 was subjected to a paint curing process carried out in a paint curing furnace 970 at approximately 160°C to approximately 200°C for approximately 15 minutes to approximately 60 minutes. In specific cases, the aluminum alloy coil 170 was subjected to either natural aging for approximately 1 week to approximately 4 weeks. Optionally, the aluminum alloy coil 170 was subjected to artificial aging at approximately 100°C to approximately 140°C for approximately 6 hours to approximately 48 hours.
[0111] Example 4: Mechanical properties of aged, highly formable, high-strength aluminum alloy Four cast aluminum alloy products were prepared using a continuous casting machine from the aluminum alloy compositions shown in Table 1 below, as in Example 4 (see Example 3).
[0112] Table 1 - Alloy composition TIFF2022513377000001.tif65152 Each alloy contains up to 0.15% by weight of impurities, with the remainder being aluminum.
[0113] Alloy B had a Zn / Mg ratio of approximately 1.29, Alloy C had a Zn / Mg ratio of approximately 1.28, Alloy D had a Zn / Mg ratio of approximately 2.16, and Alloy E had a Zn / Mg ratio of approximately 2.18. Furthermore, Alloy E was prepared using vertical semicontinuous (DC) casting, as well as homogenization, hot rolling, cold rolling, solution treatment, and artificial aging as described in Example 3. Samples taken from Alloy B, Alloy C, Alloy D, and Alloy E were subjected to one week of natural aging, four weeks of natural aging, or artificial aging at approximately 120°C for approximately 24 hours. Route 4 (see Example 3) was used with and without pre-aging. In some cases, a paint baking process was carried out at a temperature of approximately 180°C and maintained at this temperature for approximately 30 minutes.
[0114] Figures 10, 11, and 12 are graphs showing the mechanical properties of alloys B, C, D, and E prepared and treated according to the methods described herein. The alloys were cooled after solution treatment using water quenching. Alloy E was prepared according to the method described herein, including continuous casting ("Alloy E-CC") and according to the method described herein, including DC casting as described above ("Alloy E-DC"). After treatment, all alloys were subjected to pre-aging at 100°C for 2 hours ("PX: 100°C × 2 hours") or pre-aging at 80°C for 6 hours ("PX: 80°C × 6 hours"), followed by 1 week of natural aging (lower part of each histogram) and 4 weeks of natural aging (upper part of each histogram). Figure 10 shows the effect of natural aging on the longitudinal yield strength of the alloys. After 1 week of natural aging (lower part of each histogram), the longitudinal strength of each alloy was... The yield strength in the longitudinal direction was tested, and after 4 weeks of natural aging (top of each histogram), the yield strength in the longitudinal direction of each alloy was tested. As shown in Figure 10, natural aging had a slight effect on the longitudinal yield strength of the alloys, as indicated by an increase in longitudinal yield strength of approximately 5 MPa to approximately 15 MPa. Alloy E (including alloys E-CC and E-DC) showed high longitudinal yield strength after 1 week of natural aging due to rapid aging within 24 hours of solution treatment. Figure 11 shows the effect of natural aging on the uniform elongation of the alloys. The uniform elongation in the longitudinal direction of each alloy was tested after 1 week of natural aging (left histogram of each pair), and the uniform elongation of each alloy was tested after 4 weeks of natural aging (right histogram of each pair). As shown in Figure 11, natural aging had a slight effect on the uniform elongation in the longitudinal direction of the alloys, as indicated by a change in longitudinal uniform elongation of approximately 0% to approximately 5%. Figure 12 shows the effect of natural aging on the total longitudinal elongation of the alloys. The total longitudinal elongation of each alloy was tested after one week of natural aging (left histogram for each pair), and the total longitudinal elongation of each alloy was tested after four weeks of natural aging (right histogram for each pair). As shown in Figure 12, natural aging had a slight effect on the total longitudinal elongation of the alloys, as indicated by the change in total longitudinal elongation of approximately 0.3% to approximately 4%.
[0115] Figures 13 and 14 are graphs showing the effect of different cooling techniques after solution treatment (e.g., water quenching and forced air quenching described above) on the mechanical properties of alloys B, C, and D, which were prepared and treated according to Route 4 (see Example 3). After treatment, all alloys were subjected to pre-aging at 100°C for 2 hours ("PX: 100°C × 2 hours") or pre-aging at 80°C for 6 hours ("PX: 80°C × 6 hours"), followed by 1 week of natural aging (lower part of each histogram) and 4 weeks of natural aging (upper part of each histogram). Figure 13 shows the effect of natural aging on the longitudinal yield strength of alloy samples subjected to water quenching after solution treatment. Figure 14 shows the longitudinal yield strength of alloy samples subjected to forced air quenching after solution treatment. This shows the effect of natural aging. Overall, samples subjected to water quenching after solution treatment showed higher longitudinal yield strength than samples subjected to forced air quenching after solution treatment. However, alloys D and C showed only a slight change in longitudinal yield strength compared to the cooling process. Alloy B, which has a higher solute content than alloys C and D, showed approximately 30 MPa higher strength when subjected to water quenching after solution treatment than when subjected to forced air quenching after solution treatment. Furthermore, all alloys The gold sample showed a slight effect of natural aging on the longitudinal yield strength of the alloy. Figures 15 and 16 are graphs showing the effect of different cooling techniques after solution treatment (including water quenching and forced air quenching described above) on the uniform longitudinal elongation of alloys B, C, and D, prepared and treated according to Route 4 (see Example 3). After treatment, all alloys were pre-aged at 100°C for 2 hours ("PX: 100°C × 2 hours") or at 80°C for 6 hours ("PX The samples were subjected to heating (80°C for 6 hours), followed by one week of natural aging (histogram on the left for each pair), and then four weeks of natural aging (histogram on the right for each pair). Figure 15 shows the effect of natural aging on the uniform longitudinal elongation of alloy samples subjected to water quenching after solution treatment. Figure 16 shows the effect of natural aging on the uniform longitudinal elongation of alloy samples subjected to forced air quenching after solution treatment. Overall, the samples showed only slight changes in uniform longitudinal elongation compared to the cooling process.Furthermore, all alloy samples showed a slight influence of natural aging on the uniform elongation in the longitudinal direction of the alloy.
[0116] Figures 17 and 18 are graphs showing the effect of different cooling techniques after solution treatment (including water quenching and forced air quenching described above) on the total longitudinal elongation of alloys B, C, and D, which were prepared and treated according to Route 4 (see Example 3). After treatment, all alloys were subjected to pre-aging at 100°C for 2 hours ("PX: 100°C × 2 hours") or pre-aging at 80°C for 6 hours ("PX: 80°C × 6 hours"), followed by 1 week of natural aging (histogram on the left for each pair) and 4 weeks of natural aging (histogram on the right for each pair). Figure 17 shows the effect of natural aging on the total longitudinal elongation of alloy samples subjected to water quenching after solution treatment. Figure 18 shows the effect of natural aging on the total longitudinal elongation of alloy samples subjected to forced air quenching after solution treatment. Overall, the samples showed a slight change in total longitudinal elongation compared to the cooling process. Furthermore, all alloy samples showed a slight effect of natural aging on the total longitudinal elongation of the alloy.
[0117] Figures 19 and 20 are graphs showing the effect of different cooling techniques after solution treatment (including water quenching and forced air quenching described above) on the bending properties (e.g., the bending angle, referred to as "VDA angle - α(°)") of alloys B, C, and D, which were prepared and treated according to Route 4 (see Example 3). After processing, all alloys were subjected to pre-aging at 100°C for 2 hours ("PX: 100°C × 2 hours") or pre-aging at 80°C for 6 hours ("PX: 80°C × 6 hours"), followed by 1 week of natural aging (histogram on the left for each pair) and 4 weeks of natural aging (histogram on the right for each pair). Figure 19 shows the effect of natural aging on the bending properties of alloy samples subjected to water quenching after solution treatment. Figure 20 shows the effect of natural aging on the bending properties of alloy samples subjected to forced air quenching after solution treatment. Overall, the samples showed only slight changes in bending properties compared to the cooling process. Alloy B showed approximately 10° lower bending properties compared to alloys C and D due to its higher solute content. Furthermore, all alloy samples showed only slight effects of natural aging on the bending properties of the alloys.
[0118] Figures 21, 22, and 23 are graphs showing the longitudinal yield strength of alloys B, C, D, E-CC, and E-DC, which were prepared and treated according to Route 4 (see Example 3) and prepared by DC casting and treated as described above to yield alloys of different tempers (T4). In the examples in Figures 21 and 22, the alloys were cooled after solution treatment using water quenching. After treatment, all alloys were subjected to pre-aging at 80°C for 6 hours ("PX"). Alloys B, D, E-CC, and E-DC were then subjected to natural aging for 4 weeks, and alloy C was subjected to natural aging for 13 weeks to yield alloys of different tempers (bottom of each histogram, referred to as "T4"). Each alloy was further subjected to paint baking at 180°C for 30 minutes (middle of each histogram). Finally, each alloy was subjected to artificial aging (top of each histogram) at 120°C for 24 hours. Figure 21 shows the effects of paint baking and artificial aging on the longitudinal yield strength of the alloys. The longitudinal yield strength of each alloy was tested after natural aging (top of each histogram), paint baking (referred to as "PB" in Figures 21, 22, and 3, in the middle of each histogram), and artificial aging (referred to as "AA" in Figures 21, 22, and 23, in the top of each histogram). Furthermore, each sample was provided in different T6 tempers without pre-aging (circles, referred to as "T6 (no PX)"). As shown in Figure 21, paint baking (mid-section of each histogram) had diverse effects on the longitudinal yield strength of each alloy after pre-aging, most notably in alloys C and D, where paint baking increased the longitudinal yield strength by approximately 130 MPa to 145 MPa after pre-aging. Artificial aging (top of each histogram) also had diverse effects on the longitudinal yield strength of the alloys, as indicated by the increase in longitudinal yield strength of approximately 10 MPa to 70 MPa after pre-aging. As also shown in Figure 21, the pre-aging and paint baking processes did not adversely affect the ability of the alloys to achieve high strength in the T6 temper categories. Therefore, when treated according to the methods described herein, alloys exhibiting both high formability and high strength can be provided.
[0119] Figures 22 and 23 are graphs showing the effects of different cooling techniques after solution treatment (including water quenching and forced air quenching described above) on the mechanical properties of alloys B, C, and D, which were prepared and treated according to Route 4 (see Example 3). After treatment, all alloys were subjected to pre-aging at 80°C for 6 hours ("PX"). Alloys B and D were then subjected to natural aging for 4 weeks, and alloy C was subjected to natural aging for 13 weeks to obtain alloys of different tempers of T4 (bottom of each histogram, referred to as "T4"). Each alloy was further subjected to paint baking at 180°C for 30 minutes (middle of each histogram). Finally, each alloy was subjected to artificial aging at 120°C for 24 hours (top of each histogram). Figure 21 shows the effects of paint baking and artificial aging on the longitudinal yield strength of the alloys. The longitudinal yield strength of each alloy was tested after natural aging (bottom of each histogram), paint baking (referred to as "PB" in Figures 21, 22, and 3, middle of each histogram), and artificial aging (referred to as "AA" in Figures 21, 22, and 23, top of each histogram). Furthermore, each sample was provided by T6 quality without pre-aging (circle, referred to as "T6 (no PX)"). Figure 22 shows the effect of water quenching after solution treatment on the longitudinal yield strength of the alloy samples. Figure 23 shows the effect of forced air quenching after solution treatment on the longitudinal yield strength of the alloy samples. Overall, samples subjected to water quenching after solution treatment showed higher longitudinal yield strength than samples subjected to forced air quenching after solution treatment. Alloys C and B showed a high paint baking response regardless of the cooling process after solution treatment.
[0120] The microstructures of alloys B, C, and D, prepared and fabricated according to Route 4, and alloy E, prepared by the DC casting method described above, were evaluated by optical microscopy after the solution treatment process described above. Particle size and distribution, as well as crystal morphology, were analyzed. Figure 24 shows the particle size and distribution of each alloy sample. Each alloy showed similar particle size and distribution, as well as a small amount of undissolved precipitate. The dark gray particles shown in Figure 24 are Fe-containing constituent particles. Figure 25 shows the crystal structure of each alloy sample. Each alloy sample showed a recrystallized microstructure. Alloy E contained less crystal than alloys B, C, and D.
[0121] Figures 26, 27, and 28 show the effects of various solution parameters and natural aging on longitudinal yield strength, uniform elongation, and total elongation, respectively, of alloy C, which was fabricated and prepared according to Route 4 (see Example 3). Alloy C was subjected to solution treatment at 450°C with no immersion time (line with a white triangle labeled "450C no immersion" in Figures 26-28), solution treatment at 450°C with a immersion time of 2 minutes (line with a white circle labeled "450C 2 minutes" in Figures 26-28), and solution treatment at 470°C with no immersion time (line with a white square labeled "470C no immersion" in Figures 26-28). Alloy C was not subjected to pre-aging before 90 days of natural aging. As shown in Figure 26, the yield strength showed a slow increase after 30 days of natural aging. As shown in Figure 27, uniform elongation showed a decrease of approximately 5% after 90 days of natural aging. As shown in Figure 28, total elongation showed only a slight change after 90 days of natural aging.
[0122] Therefore, the alloy compositions described herein, when combined with the processing methods described herein, provide aluminum alloys with high formability and high strength.
[0123] All patents, publications, and abstracts cited above are incorporated herein by reference in their entirety. Various embodiments of the present invention have been described in order to accomplish various objectives of the present invention. It should be recognized that these embodiments are merely illustrative of the principles of the present invention. Numerous modifications and adaptations thereof will be readily apparent to those skilled in the art without departing from the spirit and scope of the present invention as defined in the following claims.
Claims
1. 1. A method for making a formable high strength aluminum alloy product, said method comprising: continuously casting a molten aluminum alloy composition to provide a cast aluminum alloy product having a casting exit temperature, said molten aluminum alloy composition comprising an aluminum alloy having at least 0.1 wt. % Zr, at least 2 wt. % Mg, and Zn as a major alloying element other than Al; cooling the cast aluminum alloy product to a temperature 20°C to 50°C below the casting exit temperature to provide a heat stabilized cast aluminum alloy product; hot rolling the heat stabilized cast aluminum alloy product to provide an aluminum alloy hot band; Coiling the aluminum alloy hot band to provide a hot band coil; Cooling the hot band coil to a temperature of 200°C to 400°C; further processing the hot band coil to provide a final gauge aluminum alloy product; and solution treating the final gauge aluminum alloy product.
2. The method of claim 1, wherein the molten aluminum alloy composition comprises a Zn to Mg ratio of 1.2 to 3.
3. 3. The method of claim 1 or 2, wherein the hot rolling comprises heating the heat stabilized cast aluminum alloy product to a hot rolling entry temperature.
4. 4. The method of any one of claims 1 to 3, wherein the hot rolling is carried out to reduce the thickness of the heat stabilized cast aluminum alloy product by at least 30%.
5. said further processing comprising: homogenizing the hot band coil to provide a homogenized hot band coil; and hot rolling the homogenized hot band coil to provide a final gauge aluminum alloy product.
6. said further processing comprising: homogenizing the hot band coil to provide a homogenized hot band coil; cooling the homogenization hot band coil; and cold rolling the homogenized hot band coil to provide a final gauge aluminum alloy product.
7. 7. The method of claim 5 or 6, wherein said homogenizing comprises heating said aluminum alloy hot band to a temperature of at least 450°C and maintaining said aluminum alloy hot band at said temperature of at least 450°C for a period of at least 90 minutes.
8. said further processing comprising:
5. The method of any one of claims 1 to 4, comprising cold rolling the hot band coil to provide a final gauge aluminum alloy product.
9. 9. The method of any one of claims 1 to 8, further comprising pre-aging the final gauge aluminum alloy product, wherein the pre-aging comprises heating the final gauge aluminum alloy product to a pre-aging temperature of from 50°C to 150°C and maintaining the pre-aging temperature for a period of from 1 to 24 hours.
10. 10. The method of any one of claims 1 to 9, further comprising aging the final gauge aluminum alloy product to achieve a yield strength of at least 400 MPa.
11. The method of claim 10, wherein the aging comprises one or more of natural aging, artificial aging, paint baking, and post-molding heat treatment.
12. 12. The method of claim 11, wherein said aging comprises natural aging, said natural aging comprising maintaining said final gauge aluminum alloy product at room temperature for a period of from 1 day to 12 weeks.
13. 13. The method of claim 11 or 12, wherein the aging comprises artificial aging, said artificial aging comprising heating the final gauge aluminum alloy product to an artificial aging temperature of from 100°C to 250°C and maintaining the artificial aging temperature for a period of from 1 hour to 72 hours.
14. 14. The method of any one of claims 11 to 13, wherein said aging comprises a paint bake, said paint bake comprising heating the final gauge aluminum alloy product to a paint bake temperature of from 75°C to 250°C and maintaining the paint bake temperature for a period of from about 15 minutes to about 3 hours.
15. 15. The method of any one of claims 11 to 14, wherein the aging comprises a post-forming heat treatment, the post-forming heat treatment comprising heating the final gauge aluminum alloy product to a post-forming heat treatment temperature of from 100°C to 250°C and maintaining the post-forming heat treatment temperature for a period of from 1 hour to 24 hours.
16. An aluminium alloy product prepared according to the method of any one of claims 1 to 15.
17. 17. The aluminum alloy product of claim 16, wherein the aluminum alloy product achieves an increased elongation and an increased yield strength after aging compared to the elongation and yield strength achieved by the aluminum alloy product before aging.
18. 18. The aluminum alloy product of claim 17, wherein the increase in elongation is at least 1%.
19. 18. The aluminum alloy product of claim 17, wherein the increase in yield strength is at least 15 MPa.
20. 20. An aluminium alloy product according to any one of claims 17 to 19, wherein the increase in elongation is at least 1% and the increase in yield strength is at least 15 MPa.